(untitled) (Research, Society and Development, 2020)
The present work sought to analyze the microbiological quality of artisanal rennet cheese produced in the rural area of ​​the municipality of Soledade, Paraíba. Due to its socioeconomic importance for the rural producer, since coalho cheese is a typical product of the Northeastern Sertão. In the state of Paraíba there are more than 50 producing municipalities, the majority of which manufacture this by hand, using raw milk as the main raw material, making it in practice a favorable source for product contamination. For this purpose, microbiological analyzes were carried out following the protocols suggested by RDC 12, of January 2, 2001 and normative instruction 62, of August 26, 2003. Seven samples from different local producers were analyzed, which were analyzed for the presence of coliforms fecal and thermotolerant, Escherichia Coli, Staphylococcus Aureus, Salmonella spp. and Listeria Monocytogenes. At the end, the cheese samples verified indicated that it was not feasible for human consumption, due to the large number of total coliforms and Escherichia coli in all samples, as well as the presence of Salmonella Spp and Listeria Monocytogenes in four of the analyzed samples. As for the presence of Staphylococcus Aureus, all were negative. Therefore, Coalho type cheese made in the rural area and sold in the city of Soledade PB, presented unfavorable conditions for trade and consequently human consumption, due to the quantity of pathogenic microorganisms found, exceeding the limit required by Brazilian legislation.